Recent progress of tree frog toe pads inspired wet adhesive materials. Issue 4 (16th September 2022) - Zhang, Yikai; Wan, Xizi; Xu, Xuetao; Teng, Peicheng; Wang, Shutao
Abstract: Wet adhesion has widespread applications in the fields of wearable electronics, medical devices and intelligent robots. In nature, many organisms have evolved with unique wet adhesion properties to adapt to complex habitats and climb in wet environments without falling. Tree frogs, as crawling masters in tropical rain forests, are representative of wet adhesion and give novel inspirations to design artificial wet adhesive materials by mimicking their specialised hexagonal structures and/or mucus composition. In this review, we first overview the research progress of tree frog toe pads from the perspective of toe pad structure and adhesion mechanism. Then, wet adhesive materials inspired by tree frog toe pads are systematically summarised from (i) the typical polymers, (ii) the preparation approaches, (iii) the adhesion test methods and (iv) the typical artificial adhesion surfaces. Third, various applications of bioinspired wet adhesive surfaces are highlighted. Finally, we present future challenges and opportunities to develop tree frog‐inspired wet adhesive materials.